2016
DOI: 10.15252/embr.201642051
|View full text |Cite
|
Sign up to set email alerts
|

A novel long intergenic noncoding RNA indispensable for the cleavage of mouse two‐cell embryos

Abstract: Endogenous retroviruses (ERVs) are transcriptionally active in cleavage stage embryos, yet their functions are unknown. ERV sequences are present in the majority of long intergenic noncoding RNAs (lincRNAs) in mouse and humans, playing key roles in many cellular processes and diseases. Here, we identify LincGET as a nuclear lincRNA that is GLN-, MERVL-, and ERVK-associated and essential for mouse embryonic development beyond the two-cell stage. LincGET is expressed in late two- to four-cell mouse embryos. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 82 publications
1
49
0
Order By: Relevance
“…Consistent with this hypothesis, transient siRNA-mediated depletion of a subset of ERVK- and MaLR-derived long noncoding RNAs (lncRNA) highly expressed in mouse ESCs leads to reduced expression of cellular pluripotency markers, suggesting that these lncRNAs exert some form of control over the maintenance of a pluripotent state [54]. Similarly, a recent biochemical study showed that a lncRNA derived from a MERV-L locus, called LincGET , is required for in vitro embryonic development to proceed beyond the 2C stage [49]. Biochemical experiments and reporter assays suggest that LincGET functions as a scaffold for the recruitment of TFs and splicing factors (Figure 3C), some of which are known to be important for embryonic development [49,55].…”
Section: Erv Choreography In Early Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this hypothesis, transient siRNA-mediated depletion of a subset of ERVK- and MaLR-derived long noncoding RNAs (lncRNA) highly expressed in mouse ESCs leads to reduced expression of cellular pluripotency markers, suggesting that these lncRNAs exert some form of control over the maintenance of a pluripotent state [54]. Similarly, a recent biochemical study showed that a lncRNA derived from a MERV-L locus, called LincGET , is required for in vitro embryonic development to proceed beyond the 2C stage [49]. Biochemical experiments and reporter assays suggest that LincGET functions as a scaffold for the recruitment of TFs and splicing factors (Figure 3C), some of which are known to be important for embryonic development [49,55].…”
Section: Erv Choreography In Early Embryonic Developmentmentioning
confidence: 99%
“…Similarly, a recent biochemical study showed that a lncRNA derived from a MERV-L locus, called LincGET , is required for in vitro embryonic development to proceed beyond the 2C stage [49]. Biochemical experiments and reporter assays suggest that LincGET functions as a scaffold for the recruitment of TFs and splicing factors (Figure 3C), some of which are known to be important for embryonic development [49,55]. …”
Section: Erv Choreography In Early Embryonic Developmentmentioning
confidence: 99%
“…The existence of such evolutionary-established mechanisms of regulation of ontogenesis with the help of TE can be confirmed if the suppression of the activity of specific TE required for further regulation of cell differentiation will stop the further development of the organism. Indeed, in experiments on mouse embryos, it was shown that depletion of the long LincGET ncRNA associated with LTR-RE leads to a complete arrest of further development at the two-cell stage (Wang et al, 2016). In this stage, many transcripts are initiated from the LTR-RE (Macfarlan et al, 2012) and are associated with enhancers that support the polypotency (Fort et al, 2014).…”
Section: Tissue-specific and Stage-specific Activation Of Transposonsmentioning
confidence: 99%
“…The literature provides enough data to suggest that transposons (TE, transposable elements) can serve as hidden genetic structures capable of changing the expression of specific genes in response to certain ES (which overcome resistance to the constancy of the phenotype). This is due to the fact that TEs play an important role in the regulation of gene expression in ontogenesis (de Souza et al, 2013;Pavlicev et al, 2015;Wang et al, 2016;Ito et al, 2017;Ramsay et al, 2017;Saze, 2018) and serve as sources of changes in epigenetic (EG) factors (Li et al, 2011;Ito, 2012;Kapusta et al, 2013;Gim et al, 2014;Cho, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…depletion of the LincGET lncRNA causes a total arrest of the late G2-phase of bicellular stage in mice. This effect is determined by LincGET inability to bind the ILF2, FUBP1and hnRNP-U proteins and form a complex necessary for the cis-regulatory activity of LTR-containing retro-ТЕ GLN, MERVL, ERVK (Wang et al, 2016). TEs can also be used as lncRNA genes, e.g.…”
Section: Transposon and Noncoding Rna Activity In Brainmentioning
confidence: 99%